Interdisciplinary Approaches to Adaptive Learning. A Look at the Neighbours First International Conference on Interdisciplinary Research on Technology, Education and Communication, ITEC 2010, Kortrijk, Belgium, May 25-27, 2010, Revised Selected Papers - Wannemacker, Stefan; Clarebout, Geraldine; Causmaecker, Patrick; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the First International Conference on Interdisciplinary Research on Technology, Education and Communication, ITEC 2010, held in Kortrijk, Belgium, in May 2010. The 11 revised full papers presented were carefully reviewed and selected from 38 submissions. The papers address all current issues within the fields of computer sciences, applied linguistics, methodology, and educational technology with special emphasis on topics such as distributed decision support, agent based systems, heuristic optimization, heuristics for data mining, distributed search, pervasive learning, mobile learning electronic language learning environments, language testing, CorpusCALL, authoring systems statistical modelling, item response theory, data mining, electronic assessment adaptive and adaptable learning environments, instructional design, game-based learning, learner characteristics, mobile learning.
Keywords: Computer science; Computer Communication Networks; Multimedia systems; Artificial intelligence; Education; Computer Science; Computers and Education; Multimedia Information Systems; User Interfaces and Human Computer Interaction; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Computer Communication Networks